He Āpiti Hono, He Tātai Hono: That Which is Joined Remains an Unbroken Line: Using Whakapapa (Genealogy) as the Basis for an Indigenous Research Framework - Graham, James (The Australian Journal of Indigenous Education, 2005)
Abstract This paper explores the notion of whakapapaas providing a legitimate research framework for engaging in research with Māori communities. By exploring the tradition and meaning of whakapapa, the paper will legitimate how whakapapaand an understanding of whakapapacan be used by Māori researchers working among Māori communities. Therefore, emphasis is placed on a research methodology framed by whakapapathat not only authenticates Māori epistemology in comparison with Western traditions, but that also supports the notion of a whakapaparesearch methodology being transplanted across the Indigenous world; Indigenous peoples researching among their Indigenous communities. Consequently, Indigenous identity is strengthened as is the contribution of the concept of whakapapato Indigenous research paradigms worldwide.